FEATURES OF THE СOURSE OF ISCHEMIC HEART DISEASE IN PATIENTS WITH COVID-19 (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The coronavirus disease 2019 (COVID-19) pandemic has been going on for more than two years and is significantly affecting routine clinical practice. Despite the numerous publications on heart damage in the acutephase of COVID-19, there is not enough data regarding the dynamics of cardiovascular system condition in coronary artery disease (CAD) patients after the infection caused by SARS-CoV-2. The infl uence of the long-term consequences of the disease on cardiovascular system condition of patients who have had infection requires careful study. Goal. To assess the clinical and laboratory picture and coronary lesion nature in CAD patients with mild or moderate course of COVID-19 infection after at least 12 weeks. Materials and methods. The analysis of clinical, laboratory parameters and coronary angiography of 118 CAD patients aged 46–67 years (mean age 60.2 ± 6.1 years) after a serologically confi rmed SARS-CoV-2 infection at the lapse of 12 weeks was carried out. The patients were divided into 2 groups: group 1 included 60 patients with a mild COVID-19, group 2 included 58 patients with a moderate COVID-19 course. Results. CAD patients with a moderate course of COVID-19 in the acute period had higher values of office blood pressure, higher incidence of uncontrolled arterial hypertension, major multivessel lesions of coronary arteries and lesions of the main vessels than CAD patients with mild COVID-19. When comparing echocardiographic parameters in patients with moderate COVID-19, the lower parameters of the left ventricular ejection fraction were found which is quite consistent with the higher NT-proBNP values in these patients. Conclusion. CAD patients, who have had moderate COVID-19 in the acute phase of infectious process, constitute a special risk group for a subsequent more severe course of the underlying disease.